THE RESULTS OF EXPERIMENTAL WORK ON THE FORMATION OF READINESS FOR SOCIAL AND EVERYDAY ORIENTATION IN OLDER PRESCHOOL CHILDREN IN ADDITIONAL EDUCATION ORGANIZATIONS - Barcaeva; Ryabova (Revista Inclusiones, 2020)
The article is aimed at the development and realization of a model for the formation of readiness for social and everyday orientation in older preschool children based on additional education, as well as at identifying the dynamics of older preschoolers’ progress in mastering said readiness. The abovementioned model is developed and its blocks are described in detail: the methodological block (includes the personality-oriented, sociocultural, systemic, activity, environmental, and anthropological approaches, the principles of integrity, scientific nature, accessibility, humanism, individualization, cooperation, creative activity, connection with life, and cultural relativity), the target block (aimed at the development of motives, interests, and needs of preschoolers), the content block (includes personal, cognitive, and activity components of social orientation readiness), the organizational and process block (includes the forms, methods, means, as well as the stages of readiness formation; pedagogical conditions for the functioning of this process based on additional education organizations), and the result and evaluation block (includes original diagnostic tools allowing one to evaluate the dynamics of the level of readiness formation).